Moral emotions in neuropsychiatry : testing FTD and Schizophrenia patients with the MEA scale. (20th December 2022) - AUGER, Raphaëlle LEROUX; Mouchabac, Stephane; Daigmorte, Chloé; GALLARDA, Thierry; Hamisultane, Jessica; Azuar, Carole
Abstract: Background: Moral emotions have a key role in human prosocial behaviors. Impaired moral emotion processing can lead to disrupted decision‐making and behavioral adaptation. Better knowledge about moral emotion processing in neuropsychiatric diseases is necessary to facilitate diagnosis and patient care. The aim of this study was to investigate and to compare moral emotion processing in patients with neurodegenerative diseases ‐behavioral fronto temporal dementia (FTD) and Alzheimer's disease (AD)‐ and patients with schizophrenia. Method: We investigated 22 FTD, 15 AD, 30 schizophrenia patients and a control group with validated task, the Moral Emotions Assessment (MEA). This tool consisted in 42 scenarios exploring positive and negative moral emotions such as admiration, gratitude, shame or anger. Subjects had to choose between several emotions the most appropriate to the context of the scenario. To control for moral specificity, we contrasted the 42 moral scenarios with 18 extra‐moral scenarios eliciting the emotions without involving any inter‐human moral context. Result: FTD patients and Schizophrenia patients were significantly impaired in moral emotion processing, when compared to healthy controls, whereas AD patients were not impaired. There was a specific impairment of moral emotions in FTD, (73.1% of correct answers VS 95.1% in control group p<0, 001) and the most impaired emotion was guilt. AD patients didn't show impairment in moral emotion processing compared to healthy controls. In Schizophrenia patients, moral emotion processing was significantly impaired (85, 8% of correct answers VS 95, 9% in control group, p<0, 001), and the most impaired emotions were anger and shame. Conclusion: Moral emotions processing seemed significantly impaired in FTD patients and schizophrenia patients, with different patterns of deficits, whereas AD patients seemed to have preserved moral cognition. These results provide a better understanding of the behavioral changes observed in FTD and schizophrenia patients.